Egotism and female managerial performance in South Africa: Evidence from SMEs in the agricultural sector - Nico van Rensburg (Taylor & Francis Group, 2021)
This study sets out to address the perceived pitfalls of egotism among female entrepreneurs in South Africa. This study further ascertains a unique strategy and group of accustomed performance factors that are believed to serve as a cognitive antidote for female entrepreneurs to consistently out-manoeuvre the dangers of egotism. This study adopted a qualitative approach in which 16 achieving female entrepreneurs were purposively selected. The primary data was collected through the application of professionally conducted semi-structured one-on-one interviews and Interpretative Phenomenological Analysis (IPA) served as the primary method of data analysis. Findings from this study prove the significant impact the effects of egotism are believed to have on entrepreneurship and managerial performance as a whole. Aspects such as continuous self-study and the establishment of a disciplined mind both surfaced as invaluable assets. Finally, results also prove that the adaptation of a neutralised mental approach to events proves to eliminate egotism as a falsely imposed performance mechanism within entrepreneurship undertaking as a whole.